2003
DOI: 10.1063/1.1609247
|View full text |Cite
|
Sign up to set email alerts
|

Elastic responses to different electric-field directions in relaxor ferroelectric Pb[(Zn1/3Nb2/3)0.91Ti0.09]O3 single crystals

Abstract: Micro-Brillouin scattering was applied to relaxor-based complex perovskite Pb[(Zn1/3Nb2/3)0.91Ti0.09]O3 (PZN–9% PT) single crystals during a polarization switching under two different electric-field directions along 〈111〉 and 〈101〉. Brillouin spectra consisted of one longitudinal and two transverse acoustic modes, and the Brillouin shift and the full width at half maximum of these modes showed clear changes near the coercive field (Ec) where the polarization reversal occurred. In particular, the lowest transve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…They showed that a successive C → T → Mc transitions occurred on the field-cooling process and unknown phase X, which is a different new phase, appeared on the zero-field cooling [11]. Brillouin scattering has been performed on PZN, PZN-4.5%PT and PZN-9%PT with near the MPB composition [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that a successive C → T → Mc transitions occurred on the field-cooling process and unknown phase X, which is a different new phase, appeared on the zero-field cooling [11]. Brillouin scattering has been performed on PZN, PZN-4.5%PT and PZN-9%PT with near the MPB composition [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The PZN has not only very good dielectric properties but also excellent piezoelectric properties. [4][5][6][7][8][9][10][11] However, synthesizing perovskite PZN or Pb(Zn 1/3 Nb 2/3 )O 3 -PbTiO 3 (PZN-PT) ceramics near morphotropic phase boundary (MPB) using a conventional ceramic process is difficult, because pyrochlore phases form easily. [12][13][14][15] Perovskite PZN and 0.9PZN-0.1PT crystals have been reported to be thermodynamically unstable over the wide range of temperatures 600-1400 • C. 13 Lim et al 14 investigated that the perovskite PZN-PT single crystals decomposed to the pyrochlore phase, PbO and ZnO during high temperature annealing, even in PbO-rich environments.…”
Section: Introductionmentioning
confidence: 99%
“…10 Detailed phase diagrams of PZN-x % PT and PMN-x % PT single crystals near MPB have been studied resently based on synchrotron x-ray measurements. [17][18][19] Since there has been no systematic investigation into the FC effects on PZN-9%PT single crystals, we examined the elastic properties of this composition in a large temperature range. These two phase transitions are known to be first-order phase transitions with noticeable thermal hysteresis.…”
Section: Introductionmentioning
confidence: 99%